2011
DOI: 10.1016/j.ijpara.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing and crossbreeding recovers deteriorated traits in laboratory cultured Steinernema carpocapsae nematodes

Abstract: The nematode Steinernema carpocapsae infects and kills many pest insects in agroecosystems and is commonly used in biocontrol of these pests. Growth of the nematodes prior to distribution for biocontrol commonly results in deterioration of traits that are essential for nematode persistence in field applications. To better understand the mechanisms underlying trait deterioration of the efficacy of natural parasitism in entomopathogenic nematodes, we explored the maintenance of fitness related traits including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Attenuation of beneficial traits, which may result from repeated sub-culturing, can jeopardize biocontrol efforts. Trait deterioration can be genetically based (e.g., inbreeding, drift, inadvertent selection), or stem from non-genetic factors (e.g., disease or nutrition) (Chaston et al, 2011;Hopper, Roush, & Powell, 1993;Tanada & Kaya, 1993). Deterioration in EPNs has been observed under laboratory conditions for various traits such as virulence, environmental tolerance, reproductive capacity, and host-finding (Bai, Shapiro-Ilan, Gaugler, & Hopper, 2005;Bilgrami, Gaugler, Shapiro-Ilan, & Adams, 2006;Shapiro, Glazer, & Segal, 1996;Wang & Grewal, 2002).…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Attenuation of beneficial traits, which may result from repeated sub-culturing, can jeopardize biocontrol efforts. Trait deterioration can be genetically based (e.g., inbreeding, drift, inadvertent selection), or stem from non-genetic factors (e.g., disease or nutrition) (Chaston et al, 2011;Hopper, Roush, & Powell, 1993;Tanada & Kaya, 1993). Deterioration in EPNs has been observed under laboratory conditions for various traits such as virulence, environmental tolerance, reproductive capacity, and host-finding (Bai, Shapiro-Ilan, Gaugler, & Hopper, 2005;Bilgrami, Gaugler, Shapiro-Ilan, & Adams, 2006;Shapiro, Glazer, & Segal, 1996;Wang & Grewal, 2002).…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
“…Both the nematodes and their bacterial symbionts may experience trait loss (Bilgrami et al, 2006;Wang et al, 2007). The cause of trait deterioration in EPNs (H. bacteriophora) was reported to be genetically based with inbreeding depression being the prominent issue (Adhikari et al, 2009;Bai et al, 2005;Chaston et al, 2011).…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
“…If the new populations prove to be superior they can be further propagated and used. Multiple selected strains with improved traits (as represented by DNA markers) but with variable genetic backgrounds should be maintained and inter-crossed to prevent trait deterioration [17, 18]. …”
Section: Methods For Trait Improvementmentioning
confidence: 99%
“…Moreover, selection of some traits can lead to inadvertent reduction of others or of overall fitness [12, 15, 16]. Inbreeding depression or other means of fitness loss during EPN-mass production or as a result of continuous laboratory culture are also concerns [17, 18]. The second major strategy to improve EPN field efficacy is to use modern genetic and molecular tools.…”
Section: Entomopathogenic Nematodes In Biological Controlmentioning
confidence: 99%
“…Genome size of these bacteria varies between 4.5 Mb (X. nematophila) and 4.8 Mb (X. szentirmaii). The GC content varies between 44.2 % (X. nematophila) and 45 % (X. bovienii) (Chaston et al, 2011;Gualtieri, Ogier, Pagès, Givaudan, & Gaudriault, 2014;Lanois et al, 2013). Analyses of these genomes has revealed that there is a large number of encoded adhesins, toxins, hemolysins, proteases and lipases, as well as a wide array of antibiotic synthesizing genes (Bode, 2009).…”
Section: Symbiotic Bacteriamentioning
confidence: 99%